MADRASAH QUALITY IMPROVEMENT THROUGH MADRASAH IBTIDAIYAH ACCREDITATION COMPANIN PROGRAM - Nugraha, Muhamad Tisna; Mansur, Mansur; Kusnayat, Agus (TARBAWY : Indonesian Journal of Islamic Education, 2021)
Abstrak. Penelitian ini membahas tentang banyaknya Madarasah Ibtidaiyah di Kabupaten Kubu Raya yang belum terakreditasi. Penelitian ini bertujuan untuk mengetahui kegiatan perencanaan program pendampingan akreditasi Madrasah Ibtidaiyah di Kabupaten Kubu Raya, dan pelaksanaannya. Metode yang digunakan dalam penelitian ini adalah pendekatan Participatory Action Research (PAR) atau juga dikenal dengan penelitian aksi bersama. Instrument atau alat pengumpulan datanya adalah observasi, wawancara, dokumentasi dan lembar penilaian. Berdasarkan hasil penelitian, maka dapat diketahui bahwa: 1) Kegiatan perencanaan progam pendampingan akreditasi madrasah dilakukan dengan workshop yang melibatkan Kepala Sekolah, Kemenag Kabupaten Kubu Raya dan prodi PGMI IAIN Pontianak. 2) Pelaksanaan program pendampingan madrasah ibtidaiyah di Kabupaten Kubu Raya dilakukan melalui 2 siklus kegiatan workshop dalam memahami 8 standar akreditasi.Â Abstract. This study discusses the number of Islamic elementary schools in Kubu Raya Regency that have not been accredited. This study aims to determine the planning activities of Madrasah Ibtidaiyah accreditation assistance programs in Kubu Raya Regency, and their implementation. The method used in this research is the Participatory Action Research (PAR) approach or also known as joint action research. Instruments or data collection tools are observations, interviews, documentation and assessment sheets. Based on the results of the study, it can be seen that: 1) The planning activities of the madrasah accreditation mentoring program were carried out by workshops involving the Principal, the Ministry of Religion of Kubu Raya Regency and the PGMI IAIN Pontianak study program. 2) Implementation of the Madrasah Ibtidaiyah mentoring program in Kubu Raya Regency is carried out through 2 cycles of workshop activities in understanding 8 accreditation standards.Â